Report on International Conference and Exhibition on Tunnelling and Underground Space 2015 (ICETUS 2015) - Ooi, Teik Aun, Ir. Dr (The Institution of Engineers, Malaysia (IEM), 2016)
Link to publisher’s homepage at http://www.myiem.org